The synergistic effect of sewage sludge and bituminous coal co-pyrolysis on bio-oil production - Nkgabane, Baatseba Pearl (Vaal University of Technology, 2023)
The application of existing thermochemical conversion technologies for co-conversion of coal and sewage sludge offers a potential route for waste valorisation, reduction of air pollution from coal processing and cost savings. Although extensive research has been conducted and reported on thermogravimetric co-pyrolysis of different types of sewage sludge and coal, there are limited studies on their co-pyrolytic products yield and quality. As a result, the aim of this project was to investigate the potential synergistic effect of sewage sludge and coal co-pyrolysis on the derived co-pyrolytic products yield and organic fraction composition when heated at slow heating rates (<10 °C/min). Coal (BC) from the Highveld coal field in South Africa (SA), anaerobically digested sewage sludge (SS) from a Gauteng wastewater treatment plant in SA and their blended samples (classified as 10C, 30C, 50C, 70C and 90C with ratios of BC: SS as 10:90, 30:70, 50:50, 70:30 and 90:10, respectively) were prepared as feedstock for the test work. The pyrolysis of BC, SS and their blended samples was studied at atmospheric pressure, different final temperatures (520, 720 and 920 °C) and under Argon (Ar) atmosphere using the North-West University (NWU) modified Fischer assay setup and a thermogravimetric analyser (TGA). The BC sample was identified as a medium rank C bituminous coal with a mean random reflectance of 0.71, vitrinite composition of 5.6 vol.% and inertinite composition of 70.0 vol.%. The SS sample consists of higher contents of volatile matter (VM), oxygen (O), nitrogen (N), sulphur (S), hydrogen (H), a higher percentage ash yield (A) and lower contents of fixed carbon (FC), carbon (C) and a lower calorific value when compared to those of the BC. The TG analysis results for the blended samples showed that there exist synergistic interactions between the BC and SS particles that favoured the production of more char than the calculated one. This could be explained by the early release of volatile compounds from the SS sample that inhibit the release of volatiles from the BC sample. The SS and BC samples have different organic and inorganic compounds in their organic carbon matrix that decompose/transform at different temperatures. The NWU modified Fischer assay pyrolysis experiments using SS, BC and their blended samples showed that the final temperature has a large effect on the derived products yields and favoured the production of char over the other pyrolytic products. During individual SS and BC pyrolysis, increasing the temperature from 520 to 920 °C decreased the char yields, increased the pyrolytic gas and water yields whilst the bio-oil and tar yield remained almost constant. The lower BC tar yield (approximately 3 wt.%) in comparison to SS bio-oil yield (approximately 21 wt.%) could be due to its’ low VM (20.9 wt.%, dry basis) and a higher inertinite content. The co-pyrolytic char yields decreased with increasing temperature but increased with increasing amount of BC for all the blends. The highest co-pyrolysis char yield of 84.4 wt.% was achieved at 520 °C with the 90C blend. With regards to the organic fraction, increasing the temperature only had a significant effect on the 50C blend with the yield decreasing from 11.5 wt.% at 520 °C to 3.5 wt.% at 720 °C and remained almost constant for the other blends. The synergistic interactions between SS and BC particles that resulted in the production of a higher organic fraction than expected were dominant at 720 °C for the 30C sample. However, the highest organic fraction yield of 20.0 wt.% was obtained at 520 °C using the 10C blend. Gas chromatography and–flame ionization detection (GC-MS & GC-FID) and simulated distillation (Sim-Dis) analyses of the co-pyrolytic organic fraction indicated that there were insignificant differences in the composition of the 10C and 30C blends at 520 °C. However, the composition of the O-containing, N-containing organic compounds and aliphatic hydrocarbons significantly decreased with increasing content of BC in the blended samples from 30C to 70C. Synergistic interactions resulted in increased aliphatic hydrocarbons, PAHs, naphtha fraction and decrease in light vacuum gas oil fraction.
M. Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Thermochemical conversion technologies; Sewage sludge; Sewage sludge pyrolysis; Wastewater and sewage sludge treatment; Bio-oil production; Synergic effect; Bituminous coal co-pyrolysis; Pyrolysis; Dissertations, Academic -- South Africa.; Sewage sludge -- South Africa.; Biomass energy.; Renewable energy sources.